Chichinmanum weamu: awajun in the National University of the Peruvian Amazon - Hidalgo Bonicelli, Alejandra (2017)
This article analyzes if life conditions in the National University of the Peruvian Amazon assured six young Awajun their well-being. It ponders several questions; what is the emic meaning of being well?, Could young migrants satisfy their socio-economic and affective needs?, which are the strategies used to perform as students? To answer these questions, a qualitative methodology and different ethnographic techniques such as interviews, focus groups, observations and life stories were used. And different actors such as student colleagues, teachers, university authorities, were observed and interviewed. The expression chichinmanum weamu, translated from Awajún as going against the current, describes a situation that many young natives who try to become graduates go through. Young Awajun thought that being good meant having all the basic services, goods and resources needed to develop as students, which also implied having fluid relationships with peers and teachers. The study reached the conclusion that young Awajun were not entirely satisfied. However, the social capital developed through the Student Organization of the Indigenous Peoples of the Peruvian Amazon did ensure their survival in Iquitos.